PENGGUNAAN ALAT PERAGA SEDERHANA TANGGA SATUAN BERAT DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN METODE DEMONSTRASI - Randi Eka Putra; Nevy Clara (LP3M Universitas Muhammadiyah Muara Bungo, 2020)
The background of this study is the low learning outcomes of mathematics subjects in grade III 88 88 of the Sungai Mengkuang. Factors that influence are because learning is still conventional, there is no involvement of students in the learning process, do not use teaching aids in the learning process and do not use demonstration methods in the learning process. Describe the results of learning mathematics class III with the application of simple props ladder unit weight using the demonstration method. This research is a classroom action research with qualitative and quantitative approaches. The subjects of the study were 27 students in grade III SD 88 / II Sungai Mengkuang. In its implementation, this research consisted of 2 cycles. Each cycle consists of 4 stages, namely action planning activities, implementation of actions, observation, and reflection in each cycle. The research data was collected based on observations, learning outcomes tests, and documentation. The results showed: 1) the application of simple props of the unit of weight by the demonstration method can improve the process of teachers and students. The process of teachers in the first cycle of 89% (good category) in the second cycle increased to 91% (very good category). The process of students in the first cycle by 81% (good category) in the second cycle increased to 92% (very good category). 2) an increase in learning outcomes that reach a value above the KKM (66) with a percentage of pre-cycle 19%, cycle I 51%, and cycle II 78%.